Yishenyangsui granule for degenerative cervical myelopathy: a randomized, double-blind, placebo-controlled trial with long-term follow-up - Yin, He; Chen, Xin; Liu, Zhiwei; Xu, Bo; Jin, Zhefeng; Liu, Yan; Qi, Baoyu; Tang, Bin; Wang, Ping; Xu, Fanping; Wei, Xu; Yu, Jie; et al. (Frontiers in Pharmacology, 2025)
ObjectiveThis randomized controlled trial aims to evaluate the efficacy and safety of Yishenyangsui granule for treating Degenerative Cervical Myelopathy.Materials and methodsA randomized, double-blind, placebo-controlled clinical trial was conducted with 152 participants recruited from three centers and randomly assigned to receive either Yishenyangsui granule or placebo. The Japanese Orthopaedic Association (JOA) score and Neck Disability Index (NDI) score were evaluated for 32 weeks. Patient-reported outcomes including surgical treatment data, re-treatment data, and patient-reported condition were collected for long-term follow-up. This trial was approved by the ethics committee of WangJing Hospital of China Academy of Chinese Medical Sciences (WJEC-KT-2016-004-P001) and was registered at the Chinese Clinical Trials Registry (ChiCTR-INR-16009723) on 03 November 2016 (Check out at https://www.chictr.org.cn/indexEN.html for a more comprehensive overview).ResultsThe results showed that the improvement in JOA score at week 8 was significantly better in the Yishenyangsui granule group than in the placebo group (1.47 vs. 0.43; P < 0.001). Furthermore, improvements in motor function of upper/lower extremities, sensory function of upper extremities, reading ability, and recreation domain scores were also significantly superior in the Yishenyangsui granule group compared to the placebo group (P < 0.05). Long-term follow-up outcomes revealed no statistical differences between groups regarding surgical treatment data or patient-reported condition (P > 0.05). However, there was a significant difference detected in re-treatment data between groups with a lower rate observed among those receiving Yishenyangsui granule compared to those receiving placebo [25 (43.10%) vs. 40 (68.97%); P = 0.033], indicating its effectiveness for treating mild-to-moderate Degenerative Cervical Myelopathy.ConclusionYishenyangsui granule was effective in treating mild to moderate Degenerative Cervical Myelopathy. The participants have improved long-term outcomes.Clinical Trials Registrationhttps://www.chictr.org.cn/indexEN.html, identifier ChiCTR-INR-16009723.